Prevalence of adiponetin gene polymorphisms among Filipino patients with coronary artery disease examined at St. Luke's Medical Center - Luz, Mark Anthony D.; Pasion, Khristine Amber C.; Alfon, Jhoe Anthony R.; Torres, Brian Carlmichael L.; Maliglig, Aubrey Anne C.; Villamejor, Shaila Lyn J.; Diaz, Justine B.; Mondragon, Miguel; Mararang, Marife P.; Sabino, Fercival B.; Asi, Joelloyd T.; Mendoza, Michael Vincent S.; et al. (2011)
The adiponectin gene located on chromosome 3q27 has been previously identified as s susceptibility locus for metabolic disorders and coronary artery disease (CAD). More than ten polymorphisms in the gene have been found and two of these, the rs2241766 (SNP45T>G) at exon 2 and in intron 2, rs1501299 (SNP276G>T), have been related to low circulating adiponectin levels that has been associated with obesity, insulin resistancee, and CAD. The allelic distribution of the SNP45 and SNP276 polymorphisms was studied in Filipino patients with CAD using polymerase chain reaction-restriction fragment length polymorphism method. The observed allelic distribution was 0.71 and 0.29 for the T and G alleles respectively in 1,012 patients genotyped for the SNP45 polymorphism and was in accordance with the Hardy-Weindberg law using X^2 test. Genotypic frequencies were 0.503, 0.41, and 0.10 for the TT, TG, and GG genotypes respectively. In comparison, the allelic distribution of the G and T alleles were 0.57 and 0.43 respectively in 754 patients genotyped for the SNP276 polymorphism. Genotypic frequencies at 0.32, 0.49, and 0.19 for the GG, TG, and TT genotpyes respectively, were obtained. Linkage between the two polymorphisms was determined. The associations of these polymorphisms as a risk factor for the development of CAD and Type 2 diabetes is currently being determined.
Keywords: Cardiovascular diseases; Diabetes; Genetic polymorphisms